2021
DOI: 10.1186/s40494-021-00544-x
|View full text |Cite
|
Sign up to set email alerts
|

Structured-light 3D scanning of exhibited historical clothing—a first-ever methodical trial and its results

Abstract: Historical costumes are part of cultural heritage. Unlike architectural monuments, they are very fragile, which exacerbates the problems of their protection and popularisation. A big help in this can be the digitisation of their appearance, preferably using modern techniques of three-dimensional representation (3D). The article presents the results of the search for examples and methodologies of implementing 3D scanning of exhibited historical clothes as well as the attendant problems. From a review of scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
11
0
5
Order By: Relevance
“…The topic of the 3D scanning of historical clothes is clearly under-explored, especially in the perspective of UN and EU initiatives and funding. Our analysis revealed that a complex and coherent methodology proposal that could address these needs is missing, and this was a tremendous motivational trigger-as a result, such methodology was proposed in another article [33]. We hope that this article offers a small but important contribution to bringing this topic to light and allotting it the importance it deserves.…”
Section: Discussionmentioning
confidence: 95%
“…The topic of the 3D scanning of historical clothes is clearly under-explored, especially in the perspective of UN and EU initiatives and funding. Our analysis revealed that a complex and coherent methodology proposal that could address these needs is missing, and this was a tremendous motivational trigger-as a result, such methodology was proposed in another article [33]. We hope that this article offers a small but important contribution to bringing this topic to light and allotting it the importance it deserves.…”
Section: Discussionmentioning
confidence: 95%
“…No que se refere ao contexto internacional, Educação patrimonial ou como a pesquisa sugere "Heritage Education", Mendoza-Garrido et al (2021) entendem como um processo que permite as pessoas compreender e se apropriar de seus bens tangíveis e intangíveis. A tecnologia é uma ferramenta corriqueira no que se refere ao patrimônio histórico, porém vem se desenvolvendo cada vez mais frente à educação patrimonial.…”
Section: Patrimonialunclassified
“…Due to the ability to accumulate traditions, socio-psychological attitudes, aesthetic needs of people, the suit can represent the world of spiritual and meaningful landmarks, everyday life and way of life, making up the cultural and historical era as a whole in its basic meanings (Kumpikaitė & Milašius, 2021;Peng & Dong, 2017). Traditional clothing, being an important factor of ethnic-identification and a repository of values and meanings of a particular culture, can form a person's personality as a bearer of the norms and values of his native culture, to establish processes of tolerance and national-cultural identity (Ermilova, 2020;Minhus & Huie, 2021;Somayaji et al, 2021) and serves as a cultural and creative object (Meng & Xiao, 2021;Montusiewicz et al, 2021;Nayak et al, 2021;Proje & Bizjak, 2018), most relevant to the design activities of the bachelor-designers suit.…”
Section: Problem Statementmentioning
confidence: 99%